Polished stone implements of the Neolithic Starčevo Culture in Northern Croatia - Težak-Gregl, Tihomila (Array, 2002)
The Starčevo Culture, the first agricultural community in northern Croatia has been archaeologically documented by more than 60 permanent settlements. They are mostly located in the southern Pannonian basin of the river sava. Favourable natural conditions of the region enabled high population density during the early and middle neolithic and so far a great number of archaeological traces. Various aspects of the Starčevo Culture have often been discussed in archaeological literature but its stone production has been neglected although the new technology of producing stone artifacts, the techniques of abrading and polishing were usually emphasized as one of the important neoolithic features. Polished stone implements, specifically the last-shaped wedges, flat axes and chisels have generally been noted in all areas of the Starčevo Culture distribution. The polished stone implements from the Starčevo settlements, such as Vinkovci-Hotel, Zadubravlje, Slavonski Brod-Galovo, Pepelana have been chosen for analysis in order to solve the problem of their function, but also to investigate and determine the possible sources of the exploited raw material and the way of its circulation among the Starčevo settlements.